Perancangan Website JAMQOS (Jamak Qoshor) Berbasis Google Sites pada Mata Pelajaran Fiqih di Kelas VII MTSN 3 Jombang - Fenda Enjelita; Hidayatur Rohmah; Chusnul Chotimah (ANWARUL, 2026)
Students’ low interest in learning the Fiqih subject, particularly the material on shalat jamak and qoshor, is one of the learning problems influenced by the dominance of lecture methods and the use of printed media that are less appealing to students. This study aims to develop the JAMQOS (Jamak Qoshor) website based on Google Sites for the Grade VII Fiqih subject at MTsN 3 Jombang and to determine students’ responses to the developed media. This study used the Research and Development (R&D) method with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of media experts, material experts, and 47 Grade VII students of MTsN 3 Jombang. Data were collected through observation, interviews, documentation, and questionnaires, and were then analyzed using quantitative descriptive analysis techniques. The results showed that the JAMQOS website obtained a media expert validation score of 97% and a material expert validation score of 87.5%, both of which were in the highly valid category. Students’ responses to the use of the media reached 91.13%, categorized as strongly agree. These findings indicate that the JAMQOS website is feasible for use as Fiqih learning media on the material of shalat jamak and qoshor. The conclusion of this study affirms that the use of Google Sites can support more interactive and engaging Fiqih learning and help students understand the material more effectively. The implication of this study is the availability of an alternative technology-based learning medium that teachers can use to improve the quality of Fiqih learning in the digital era.